The Communication Solution for LTE System under Radar Interference Circumstance - Hang Zheng; Yunjie Li; Yunpeng Zhu (International Journal of Antennas and Propagation)
The interferences of radar and communication system coexistent environment are analyzed in this paper, and an attractive detection mechanism of the radar video signal and proportional fair scheduling algorithm based on channel sensing are proposed to realize the communication by using radar radiant intermissions. And the simulation is designed based on the proposed model to test this plan. The simulated results show that the packet scheduling algorithm is an excellent candidate for the communication solution for LTE system under radar radiant intermissions.